Fabrication of porous silicon nanostuctures chemical sensor / Mohd Husairi Fadzilah Suhaimi - Fadzilah Suhaimi, Mohd Husairi (2010)
Porous Silicon Nanostructures (PSiN) was prepared by electrochemical etching using ptype Si wafer substrate with constant current density, 20 mA/cm2. Ethanoic hydrofluoric acid (HF) 48% electrolyte and ethanol (C2H5OH) at ratio 1:1 electrolyte was used. The sample was characterized by using Photoluminescence (PL) spectrum. Porous silicon nanostructures (PSiN) chemical sensor was fabricated by using sputtering technique (gold) to prepare metal contact. This metal was being prepared on the samples as an electrode of sensor and increase sensitivity of sensor. Finally, sample was tested with potassium phosphate (K2HO4) at different concentration under I-Vsystem. The result shows that when the potassium phosphate diffuses into a pore, the resistance of porous silicon nanostructures (PSiN) was decreased drastically at about 81.82%. It was also found that the resistance became stable at certain point after solution dropped. Resistance (average) of PSiN decrease with increase of chemical solution concentration dropped. So it concluded that the porous silicon nanostructures sensor is able to detecting the chemical solution.